Instead of a diary or: biography and manuscripts (on Tadeusz Konwicki`s works) - Kaniecki, Przemysław (Biografie nieoczywiste: Przełom, kryzys, transgresja w perspektywie interdyscyplinarnej, 2018)
The text refers to the specific technique applied in gathering materials for his writings by Tadeusz Konwicki: notes and comments made on the loose pieces of paper as well as reverse sides of previous works for example screenplays or reviews. There are personal keys, descrambling the contexts of Konwicki’s biography with scenes from his works, some of them revealed in archives straightforwardly. Not being a diary they may be treated as a kind of descriptive material and also as a personal testimony of a writer.